Case report: Detecting giant cell arteritis in [68Ga]Ga-DOTA-Siglec-9-PET/CT - Petzinna, Simon M.; Küppers, Jim; Schemmer, Benedikt; Kernder, Anna L.; Bauer, Claus-Jürgen; von der Emde, Leon; Salam, Babak; Distler, Jörg H. W.; Winklbauer, Anja; Essler, Markus; Schäfer, Valentin S. (Frontiers in Immunology, 2024)
ObjectivesThis study aimed to evaluate the diagnostic utility of [68Ga]Ga-DOTA-Siglec-9 positron emission tomography-computed tomography (PET/CT) in assessing disease activity in a patient experiencing a relapse of giant cell arteritis (GCA).Case presentationA 90-year-old male patient with GCA, diagnosed in 2018, was enrolled. Demographic data, disease history, and laboratory parameters, including soluble VAP-1 (sVAP-1) levels, were recorded. The patient underwent a [68Ga]Ga-DOTA-Siglec-9 PET/CT scan. Additional imaging assessments included vascular ultrasound of the superficial temporal arteries, their branches, and the facial, axillary, subclavian, carotid, and vertebral arteries, along with magnetic resonance imaging (MRI) of the aorta.The patient’s sVAP-1 level was 284 ng/ml compared to 123 ng/ml in the control group (SD ± 55). The [68Ga]Ga-DOTA-Siglec-9 PET/CT scan revealed increased tracer uptake (SUVmax) in the subclavian artery (2.5), aortic arch (2.9), and heart (2.9). Notably, the increased uptake in the descending aorta (3.5) abruptly diminished to 2.2 when passing the diaphragm, with no changes in vessel caliber observed in CT. The injection of [68Ga]Ga-DOTA-Siglec-9 was well tolerated. Aortic MRI revealed no signs of inflammatory involvement.ConclusionsThis study introduces the first application of [68Ga]Ga-DOTA-Siglec-9 PET/CT in a patient with GCA experiencing a relapse, revealing enhanced tracer uptake in the subclavian artery and aortic arch with a localized and abrupt reduction, absent in conventional imaging. These findings suggest that [68Ga]Ga-DOTA-Siglec-9 PET/CT has significant potential for precise, inflammation-specific detection of affected vascular tissue in GCA during relapse.